Two-prong splint in the treatment of proximal humeral fracture - Serin, E; Karatosun, V; Balci, C; Köseoglu, HC; Ersoy, HH (Springer Verlag, 1999)
Twenty-nine patients with two-, three- and four-part proximal humeral fractures were treated by two-prong splint. At the latest follow-up, 22 patients had excellent and satisfactory results according to the Neer criteria, with only two failures. Avascular necrosis was detected in only one patient. Given these results, we conclude that the present method can be the treatment of choice for these injuries.
Keywords: Conservative Treatment